Al-‘Urf dan Al-‘Adah: Relevansi dan Tantangannya dalam Pembentukan Hukum Ekonomi Islam - Ian ian Alfian; Nurhayati Nurhayati; Tuti Anggraini; Ahmad Riyansyah (Universitas Muhammadiyah Makassar, 2024)
This research discusses the relevance and challenges of al-‘Urf and al-‘Adah in the context of rapid fintech development and globalization. Al-‘Urf, the commonly accepted customs within society, and al-‘Adah, local traditional practices, serve as secondary sources of law in Islam that provide flexibility in adapting Sharia law to social and economic changes. The advancement of technology and globalization has created new dynamics in economic practices that do not always align with classical Islamic law. Challenges such as cashless transactions, peer-to-peer lending, and digital investments often require new assessments through the principles of al-‘Urf and al-‘Adah to remain by Sharia. This research uses a qualitative approach through interviews and literature studies to identify the relevance, challenges, and solutions for applying al-‘Urf and al-‘Adah in the digital context. The research findings indicate cross-sector collaboration between scholars, academics, and business practitioners is necessary to establish adaptive Sharia standards. By recognizing new practices that do not contradict Islamic principles, al-‘Urf and al-‘Adah have the potential to strengthen justice and ethics in fintech transactions, as well as support the sustainability of the sharia economy in the global era.